2016
DOI: 10.1016/j.qref.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Banking performance and industry growth in an oil-rich economy: Evidence from Qatar

Abstract: Available online xxx JEL classification: G2 L1 L2 O4 a b s t r a c tThis article investigates whether bank performance measures of competition, efficiency, profitability and stability are contributory to industry growth for oil-rich countries. Qatar is chosen as a case study. The real growth of value added for the 42 non-oil sub-sector industries is regressed on the banking performance, together with the quantity-based indicators by taking account of the degree of external finance-dependence over the economica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…In contrast, Cetorelli and Gambera (2001) provide evidence that bank concentration promotes the growth of those firms that are more in need of external finance by facilitating credit access of young firms in a sample of 41 countries, in line with the information hypothesis. The latter is confirmed by Gonzalez and Gonzalez (2008) in a cross-country setting as well as by Mirzaei and Moore (2015) for Qatar.…”
Section: Introductionsupporting
confidence: 60%
“…In contrast, Cetorelli and Gambera (2001) provide evidence that bank concentration promotes the growth of those firms that are more in need of external finance by facilitating credit access of young firms in a sample of 41 countries, in line with the information hypothesis. The latter is confirmed by Gonzalez and Gonzalez (2008) in a cross-country setting as well as by Mirzaei and Moore (2015) for Qatar.…”
Section: Introductionsupporting
confidence: 60%
“…Building upon the above discussion and the results of prior studies (e.g., Beck et al, 2000;Ductor and Grechyna, 2015;Kim et al, 2016;Mirzaei and Moore, 2016;Pang and Wu, 2009) that provide empirical evidence for the positive effect of banking sector development on industrial and economic growth, we argue that the effects of banking sector development on economic growth at an industry level are conditional on financial resource allocation to foster the growth of the industry. A significant role of the financial sector in economic development is the allocation of capital to investment activities with highest returns (Greenwood and Smith, 1997;King and Levine, 1993b).…”
Section: Hypothesis Developmentmentioning
confidence: 59%
“…Similarly, Pang and Wu (2009) find that bank performance plays an important role for industries that are more reliant on external finance. In a recent study, Mirzaei and Moore (2016) find that the impact of credit provided by the banking sector on industry growth (i.e., the growth of 42 non-oil industry sub-sectors) is positive and statistically significant at the 10% level for the case of Qatar during 2000-2006, suggesting that credit allocation of banks (i.e. quantity of finance) may matter for industrial growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Mirzaei and Moore (2016) made a study of the banking sector in Qatar. By using regression analysis technique, they identified that industry growth improves the performance of the banks.…”
Section: Literature Reviewmentioning
confidence: 99%